Raccomandazione UNESCO 2023: Un Approccio transdisciplinare all’Educazione alla Pace che coinvolge anche i giovani - Guetta, Silvia (Studi sulla Formazione/Open Journal of Education, 2024)
The UNESCO Recommendation on Education for Peace, adopted in November 2023, highlights the need to improve educational proposals by emphasizing the ability to integrate the quality of human relationships with knowledge and skills from an interdisciplinary and transdisciplinary perspective. In focusing on the unique aspects of the UNESCO document, the contribution will refer to the various ways and meanings used to define education for peace and will conclude with a reflection on the importance of involving the youth in this process.